The early postnatal period: Exploring women's views, expectations and experiences of care using focus groups in Victoria, Australia - Rayner Jo; McLachlan Helen L; Forster Della A; Yelland Jane; Gold Lisa; Rayner Sharon (BMC, 2008)
Abstract Background There is growing evidence from Australia and overseas that the care provided in hospital in the early postnatal period is less than ideal for both women and care providers. Many health services face increasing pressure on hospital beds and have limited physical space available to care for mothers and their babies. We aimed to gain a more in-depth understanding of women's views, expectations and experiences of early postnatal care. Methods We conducted focus groups in rural and metropolitan Victoria, Australia in 2006. Fifty-two people participated in eight focus groups and four interviews. Participants included eight pregnant women, of whom seven were pregnant with their first baby; 42 women who were in the postpartum period (some up to twelve months after the birth of their baby); and two partners. All participants were fluent in English. Focus group guides were developed specifically for the study and explored participants' experiences and/or expectations of early postnatal care in hospital and at home, with an emphasis on length of hospital stay, professional and social support, continuity of care, and rest. Discussions were audio-taped and transcribed verbatim. A thematic network was constructed to describe and connect categories with emerging basic, organizing, and global themes. Results Global themes that emerged were: anxiety and/or fear; and the transition to motherhood and parenting. The needs of first time mothers were considered to be different to the needs of women who had already experienced motherhood. The women in this study were generally concerned about the safety of their new baby, and lacked confidence in themselves as new mothers regarding their ability to care for their baby. There was a consistent view that the physical presence and availability of professional support helped alleviate these concerns, and this was especially the case for women having a first baby. Conclusion Women have anxieties and fears around early parenting and their changing role, and may consider that the physical availability of professional care providers will help during this time. Care providers should be cognisant of these potential issues. It is crucial that women's concerns and needs be considered when service delivery changes are planned. If anxiety around new parenting is a predominant view then care providers need to recognise this and ensure care is individualised to address each woman's/families particular concerns.